THE DEGRADATION OF METHYLENE BLUE OVER M2TiO4 SPINEL PHOTOCATALYST (Sciences & Technology. A, exactes sciences, 2014)
Heterogeneous photocatalysis is an advanced oxidation process (AOP) which has been widely studied by numerous researchers in the world and is used to degrade or remove a wide range of pollutants in water and air. In this study, the photocatalytic oxidation and mineralization of methylene blue in aqueous catalyst suspensions of coprecipitated cobalt titanium oxide has been carried out in a helical reactor. The photodegradation was investigated using two kinds of irradiation lamps one emitting at 254 nm and the other emitting at 365 nm. Results showed that photodegradation is an effective method for the removal of MB from wastewaters. The efficiency of the process depends strongly on the experimental conditions of synthesis. We observed that 40 % of pollutant was degraded after 3 hours of UV irradiation.